African-American community attitudes and perceptions toward schizophrenia and medical research: an exploratory study. - Hamilton, Lynnae A. (National Medical Association, 2006)
INTRODUCTION: Ensuring adequate representation of all demographic groups in medical research is necessary in order to ensure that the benefits associated with participation are equitably shared. Mental health research is unique in that the stigma associated with mental illness, such as schizophrenia, further hinders participation. Using focus groups, we set out to explore the attitudes and views of African Americans with regard to schizophrenia and medical research. METHODS: Four focus group discussions were conducted, with 23 participants divided into two groups of working and retired adults, and two groups of full- and part-time students selected from inner-city residents of Birmingham, AL, and surrounding counties. Data obtained were analyzed using the content analysis method. RESULTS: Diverse views were expressed about the cause of mental illness, and much of this was influenced by cultural beliefs. There was considerable misunderstanding of schizophrenia, and the majority of participants described the disease in terms of positive symptoms only. Whereas for older participants the Tuskegee syphilis study experience was an important factor in their reluctance to participate in medical research, younger participants expressed no knowledge of the study. Among younger participants an assumed level of social distrust was evident, with prominent fear of participating in research that employs physically intrusive methods. CONCLUSION: The provision of accurate information through trusted community sources and open dialogue will help to dispel myths, correct faulty assumptions and increase African-American participation in schizophrenia research.